Essential Oil-Bearing Plants From Balkan Peninsula: Promising Sources for New Drug Candidates for the Prevention and Treatment of Diabetes Mellitus and Dyslipidemia - Heghes, Simona Codruta; Filip, Lorena; Vostinaru, Oliviu; Mogosan, Cristina; Miere, Doina; Iuga, Cristina Adela; Moldovan, Mirela (Frontiers in Pharmacology, 2020)
Metabolic diseases like diabetes mellitus or dyslipidemia have a complex etiology characterized by the interference of genetic predisposition and environmental factors like diet or lifestyle. Over time they can cause significant vascular complications, leading to dysfunction or failure of key organs (brain, heart), with possible fatal consequences or a severe reduction of life quality. Although current authorized drugs may successfully control blood glucose or cholesterol level, their use is often associated with severe side effects, therefore the development of new drug candidates is necessary for a better management of metabolic diseases. Among potential new drug sources, aromatic plants rich in essential oils like Melissa officinalis L., Mentha x piperita L., Cuminum cyminum L. or Pistacia lentiscus L. var. chia are very promising due to their diverse chemical composition and multiple mechanisms of action. This review describes a series of recent experimental studies investigating antidiabetic and hypolipemic effects of essential oils extracted from several aromatic plant species with an ethnopharmacological relevance in the Balkan peninsula. The pharmacological models used in the studies together with the putative mechanisms of action of the main constituents are also detailed. The presented data clearly sustain a potential administration of the studied essential oils for the prevention and treatment of metabolic diseases. Further research is needed in order to ascertain the therapeutic importance of these findings.